Interaction of Water and Fiber Free and Fiber Reinforced Acrylic Resins: Studied by 400 MHz NMR - Seyfioglu Polat, Zelal; Halil Tacir, Ibrahim; Dundar Yilmaz, Berivan; Korunur, Sibel (Asian Journal of Chemistry, 2011)
There is no report is available on the interaction of polymerized acrylic resin materials with water studied by high resolution NMR. In this study, the chemical shifts of NMR peaks of water interacting with different types of polymerized acrylic resin materials were compared. Two different types of polymers obtained by heat and microwave, were selected. Each NMR sample was prepared by mixing the dusty materials and 1 mL of a mixture of H2O (80 %) and D2O (20 %). The water proton signals in samples were measured by 400 MHz NMR. The data was divided into four groups. The chemical shifts of microwave acrylic resin (group 3) was higher than that of microwave acrylic resin reinforced with glass fibers (group 4), while the chemical shift of heat cured acrylic resin (group 1) was higher than that of heat cured acrylic resin reinforced with glass fibers (group 2). Furthermore, the chemical shifts of material polymerized by microwave are higher than those polymerized by injection (group 3 > group 1, and group 4 > group 2). Data shows that different type of polymerized acrylic resin materials can be differentiated by chemical shift measurements.